A Discussion of Maximin - Vitaly Pruzhansky (Tinbergen Institute, 2004)
This paper builds on one of the results of Pruzhansky [22], namely that maximin strategies guarantee the same expected payoffs as mixed Nash equilibrium strategies in bimatrix games. We present a discussion on the applicability of maximin strategies in such class of games. The usefulness of maximin is illustrated from both positive and normative viewpoints. Examples are provided.
Keywords: C72; 330; Bounded rationality; common knowledge of rationality; correlated equilibria; rationalizability; uncertainty aversion; Spieltheorie